Предмет: Алгебра, автор: What02

Lim= 3x^2-2x-8/3x^2-5x-12
x->(-4/3)

Ответы

Автор ответа: crdd
0
 lim_{x to - frac{4}{3} }  frac{3 x^{2} -2x-8}{3 x^{2} -5x-12} = lim_{x to - frac{4}{3} }  frac{3(x-2)(x+ frac{4}{3}) }{3(x-3)(x+ frac{4}{3}) } = lim_{x to - frac{4}{3} }  frac{(x-2)(3x+4)}{(x-3)(3x+4)} =
 lim_{x to - frac{4}{3} }  frac{x-2}{x-3} = frac{- frac{4}{3}-2 }{- frac{4}{3}-3 }= frac{10}{13}
Автор ответа: Дмитрий1425
0
разные ответы
Автор ответа: What02
0
какой правильный
Похожие вопросы
Предмет: Математика, автор: salaeva1988